2017
DOI: 10.1515/psr-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Combining catalytical and biological processes to transform cellulose into high value-added products

Abstract: AbstractCellulose, the most abundant polymer of biomass, has an enormous potential as a source of chemicals and energy. However, its nature does not facilitate its exploitation in industry. As an entry point, here, two different strategies to hydrolyse cellulose are proposed. A solid and a liquid acid catalysts are tested. As a solid acid catalyst, zirconia and different zirconia-doped materials are proved, meanwhile liquid acid catalyst is carried out by sulfuric acid. Sulfuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Conversion of biomass to biofuels by combined catalytic and biological processes (Adapted from[76]). …”
mentioning
confidence: 99%
“…Conversion of biomass to biofuels by combined catalytic and biological processes (Adapted from[76]). …”
mentioning
confidence: 99%
“…5-HMF yield reached 3.76% at 1.4 MPa autogenic pressure, 463 K and cellulose conversion 52.18%. Gavilà et al [41] reported transformation of microcrystalline cellulose to 5-HMF at 453 K, pressure 3 MPa. The selectivity of the target product was ~20.6%.…”
Section: Perspectives Of Zro2 Catalystsmentioning
confidence: 99%
“…Table 1 presents data on the processing of cellulose and cellulose-containing biomass in the presence of catalysts based on ZrO 2 . In general, in the presence of the proposed catalytic systems, the yields of glucose and 5-HMF can reach 12.7 and 20.6%, respectively, at temperatures of 453-523 K [38][39][40][41][42][43][44][45]. The use of a cocatalyst such as sulfuric acid can improve the efficiency of the dual catalyst system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this paper we also aimed to assess the effectiveness and feasibility of the surface cell immobilization of a co-culture (1:1) of Enterobacter and Citrobacter sp on four different porous solid supports: maghemite (Fe 2 O 3 ), activated carbon (AC), silica gel (SiO 2 ) and alumina (γ-Al 2 O 3 ) via batch dark fermentation. These supports are selected because they have been proven to provide good surface area attachment sites in catalytic processes and cell immobilization [35,36]. Some previous studies also show these kinds of supports will stimulate cell growth and hydrogen production, provide buffer capacity, and enhance cell retention times.…”
Section: Introductionmentioning
confidence: 99%